Perancangan Sistem Manajemen Mutu ISO 9001:2008 untuk Supporting Department di PT. X - Teja, Erwin Hermawan; Yang Aysia, Debora Anne (Jurnal Titra, 2015)
PT. X is a PVC pipe factory that esthablised since 31st August 2013. PT. X not yet has standart for all itâs process, and supporting Department is one part of the company.ISO 9001:2008 is chosen to be applied as standard in Supporting Department. Initial mapping show that current condition of the company still 36,4% match to ISO 9001:2008 requirement.Step for Designing ISO 9001:2008 is preparation step, initial mapping, documentation step, and final mapping. Comparison result between initial mapping and final mapping show matchâs escalation as much as 34% from 36,4% to 70,5%